Augmenting Amyloid PET Interpretations With Quantitative Information Improves Consistency of Early Amyloid Detection. (August 2017) - Harn, Nicholas R.; Hunt, Suzanne L.; Hill, Jacqueline; Vidoni, Eric; Perry, Mark; Burns, Jeffrey M.
Abstract : Purpose: Establishing reliable methods for interpreting elevated cerebral amyloid-β plaque on PET scans is increasingly important for radiologists, as availability of PET imaging in clinical practice increases. We examined a 3-step method to detect plaque in cognitively normal older adults, focusing on the additive value of quantitative information during the PET scan interpretation process. Methods: Fifty-five 18 F-florbetapir PET scans were evaluated by 3 experienced raters. Scans were first visually interpreted as having "elevated" or "nonelevated" plaque burden ("Visual Read"). Images were then processed using a standardized quantitative analysis software (MIMneuro) to generate whole brain and region of interest SUV ratios. This "Quantitative Read" was considered elevated if at least 2 of 6 regions of interest had an SUV ratio of more than 1.1. The final interpretation combined both visual and quantitative data together ("VisQ Read"). Cohen kappa values were assessed as a measure of interpretation agreement. Results: Plaque was elevated in 25.5% to 29.1% of the 165 total Visual Reads. Interrater agreement was strong (kappa = 0.73–0.82) and consistent with reported values. Quantitative Reads were elevated in 45.5% of participants. Final VisQ Reads changed from initial Visual Reads in 16 interpretations (9.7%), with most changing from "nonelevated" Visual Reads to "elevated." These changed interpretations demonstrated lower plaque quantification than those initially read as "elevated" that remained unchanged. Interrater variability improved for VisQ Reads with the addition of quantitative information (kappa = 0.88–0.96). Conclusions: Inclusion of quantitative information increases consistency of PET scan interpretations for early detection of cerebral amyloid-β plaque accumulation.